Ileocolonic transposition in an HIV patient with an esophageal stricture: A case study - Handaya, Adeodatus Yuda; Andrew, Joshua; Susilo, Naufal Caesario Jouhari; Subroto, Polycarpus David; Azriel Farrel Kresna Aditya; Prakosa, Yovan Indra Bayu; Arianda, Daldy; Tyanti, Belvia Adelaida Maiya (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Introduction: Esophageal strictures in patients with HIV (Human immunodeficiency virus) are poorly understood in terms of pathogenesis, prevalence, incidence, and surgical management. Case Presentation: This case study is a 50-year-old man who has had trouble swallowing for ten months, which has left him unable to swallow for the past nine months. Clinical examination revealed thoracic esophageal constriction ranging from Vertebra thoracal (VTh) 4-5. Endoscopic findings revealed a convoluted, constricted lumen that impeded scope passage. A contrast-enhanced computed tomography (CT) scan on eight months ago revealed esophageal constriction, with suspicions of tuberculoma and fibrosis in the right upper lung. Reactive HIV results prompted anti-HIV therapy, supported by fine needle aspiration biopsy (FNAB) results, which demonstrated no evidence of malignancy but indicated granulomatous inflammation. Preoperative evaluations, including negative interferon-gamma release assay (IGRA) and sputum Acid-Fast Bacilli (AFB) tests, cleared the way for a three-hour ileocolonic transposition procedure. The procedure involved median and substernal incisions, dissection of the terminal ileum and the right colon as a graft, retrosternal tunnelling, and anastomosis with cervical oesophagus, which resulted in positive outcomes. A week later, the patient reported increased comfort, recovered eating and drinking abilities, and successful surgical incision healing. Conclusion: The ileocolonic transposition appears to be a potential therapeutic option. This safe and effective alternative not only addresses dysphagia but also improves the overall quality of life.